Changes in Functional Compounds, Volatiles, and Antioxidant Properties of Culinary Herb Coriander Leaves (Coriandrum sativum) Stored Under Red and Blue LED Light for Different Storage Times - Shoko, Tinotenda; Manhivi, Vimbainashe E.; Mtlhako, Malebo; Sivakumar, Dharini (Frontiers in Nutrition, 2022)
This study evaluated the influence of red (630–640 nm) and blue (450 nm) light-emitting diodes (LED) lights on the changes in antioxidant constituents, activity, volatile compounds, and overall acceptability of Coriander leaves (Coriandrum sativum) during post-harvest storage. Coriander leaves are harvested at commercial maturity, packed in polyethylene terephthalate punnets, and exposed for 2 h to the red LED or blue LED lights separately during storage at 5°C and 85% RH up to 9 days. Coriander leaves exposed to the white light (2 h) and continuous darkness served as controls. Samples were removed from cold storage at 3, 6, and 9 days to determine the antioxidant constituents, their activity, retention of volatile compounds, and overall acceptance. Coriander leaves exposed to red and blue LED lights for 2 h showed a commercially allowable mass loss of up to 9 days compared to the other treatments. Compared to those exposed to red LED light (2 h) and the control, leaves exposed to blue LED light for 2 h and stored for 3–9 days showed a reduction in colour change (ΔE). The β-carotene content significantly peaked at 44.55% on day 6 in coriander leaves exposed to the red LED light. However, leaves exposed to blue and red LED light showed an increase in total phenolic content by 9.34 and 6.39% on day 9, respectively. Exposure to blue LED lights increased the antioxidant activities (DPPH, ABTS, and FRAP), quercetin content, and the concentration of typical coriander aroma, 2-tridecenal, 2-dodecenal, (E), and Z-9-19 hexadecenal on day 9. Coriander leaves exposed to blue LED light (2 h) and stored up to day 9 scored a higher acceptance level by the panellists. Thus, blue light LED treatment during post-harvest storage can be recommended to retain the antioxidant property of coriander leaves.